2007
DOI: 10.4097/kjae.2007.53.3.s22
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Midazolam Added to Bupivacaine Prolongs the Duration of Spinal Blockade to T10 Dermatome in Orthopedic Patients

Abstract: Background: Although the intrathecal (IT) administration of midazolam has been reported to have analgesic effect in humans, it is not clear whether IT midazolam can prolong the duration of sensory block to T10 dermatome that is required block level for lower extremity surgery. The effect of 1 or 2 mg of IT midazolam added to bupivacaine on the duration of spinal anesthesia to T10 were examined in orthopedic patients.Methods: Sixty six adult patients were randomly allocated to receive 11 mg of intrathecal 0.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Similar observations were reported by previous studies (12, 31). Other than cesarean patients, similar observations were also provided for patients undergoing orthopedic and other types of surgeries (29, 32). …”
Section: Discussionmentioning
confidence: 72%
“…Similar observations were reported by previous studies (12, 31). Other than cesarean patients, similar observations were also provided for patients undergoing orthopedic and other types of surgeries (29, 32). …”
Section: Discussionmentioning
confidence: 72%
“…Similar observations were reported by previous studies (12,31). Other than cesarean patients, similar observations were also provided for patients undergoing orthopedic and other types of surgeries (29,32).…”
Section: Discussionmentioning
confidence: 83%
“…Similar observations were found in the previous literature. [14][15][16][17][18][19][20] We found that the VAS score of patients in both groups was equal. In the current study we observed that the participants receiving 1 ml of 0.5% heavy bupivacaine and 0.4 ml (2mg) of preservative-free midazolam intrathecally presented prolonged and postoperative effect of bupivacaine as compared to patients in the other group.…”
Section: Discussionmentioning
confidence: 99%